REVIEW OF THE SPORODERM ULTRASTRUCTURE OF MEMBERS OF THE ASTERALES - Polevova S.V. (My University, 2006)
Palynomorphological characteristics of the order Asterales are discussed. Particular attention is paid to the pollen morphology of basal families of this group and to that of problematic taxa that are considered as sister groups to the group under study. Ultrastructurally similar sporoderms of several families, including (1) Asteraceae, Calyceraceae, and Goodeniaceae; (2) Campanulaceae, Phellinaceae, and Menyanthaceae; (3) Rousseaceae, Abrophyllaceae, and Columelliaceae, are described. Pollen grains of Alseuosmiaceae and Stylidiaceae show unique ultrastructural features of the exine. © Pleiades Publishing, Inc. 2006.
Keywords: ASTERALES; PHYLOGENETIC SYSTEMATICS; POLLEN GRAINS; ULTRASTRUCTURE